2021
DOI: 10.1038/s41598-021-03909-1
|View full text |Cite
|
Sign up to set email alerts
|

A selective CuII complex with 4-fluorophenoxyacetic acid hydrazide and phenanthroline displays DNA-cleaving and pro-apoptotic properties in cancer cells

Abstract: The thin line between efficacy and toxicity has challenged cancer therapy. As copper is an essential micronutrient and is important to tumor biology, CuII complexes emerged as an alternative to chemotherapy; however, its biological properties need to be better understood. Thus, we report in vitro the antitumor effects of two CuII complexes named [Cu(4-fh)(phen)(ClO4)2] (complex 1) and [Cu(4-nh)(phen)(ClO4)2]·H2O (complex 2), in which 4-fh = 4-fluorophenoxyacetic acid hydrazide; 4-nh = 4-nitrobenzoic hydrazide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
3
6
0
Order By: Relevance
“…Various studies on copper(II) complexes with N-N heterocycle ligands have indicated their potential antitumor activity in the micromolar range [16,18,[49][50][51]. Similar results were reported for complexes with both N-N heterocycle and Hbzac, such as ( 1) and (3), which were significantly more cytotoxic against MKN-45 cells than 5-fluorouracil after 48 h of incubation [25].…”
Section: Antiproliferative Activitysupporting
confidence: 64%
“…Various studies on copper(II) complexes with N-N heterocycle ligands have indicated their potential antitumor activity in the micromolar range [16,18,[49][50][51]. Similar results were reported for complexes with both N-N heterocycle and Hbzac, such as ( 1) and (3), which were significantly more cytotoxic against MKN-45 cells than 5-fluorouracil after 48 h of incubation [25].…”
Section: Antiproliferative Activitysupporting
confidence: 64%
“…[64] For example, a selective Cu(II) complex with 4-fluorophenoxyacetic acid hydrazide and phenanthroline, Cu(II) complexes, [Cu(4fh)(phen)(ClO 4 ) 2 ], showed significant anticancer characteristic by induced DNA-damage, led to G0/G1 arrest and triggered apoptosis. [53] Three mononuclear Cu(II) chloro-complexes containing NÀ S donor Schiff base ligands, [Cu(pabt)Cl], [Cu(pma)Cl], and [Cu(pdta)Cl]Cl had been demonstrated to bind and cleavage DNA, causing cell apoptosis. The chiral Cu(II) complexes [Cu(phen…”
Section: Copper Complexes Target Dnamentioning
confidence: 99%
“…Again, in vitro antitumor effects of a Cu( ii ) complex, [Cu(4-fh)(phen)(ClO 4 ) 2 ], had been reported to act against melanoma B16F10 cells through DNA-damage, G0/G1 cell cycle arrest and triggered apoptosis. 57 Reports on promising in vitro anti-proliferative efficacy of copper( ii ) complexes against lung carcinoma cell NCI-H460 are also there. For ready reckoning, [Cu (L1)Cl]Cl·2H 2 O induced cell death by apoptosis via cell cycle arrest in sub-G1 populations, plasma membrane blebbing, fragmentation and condensation of chromatin, alterations in mitochondria along with distinct changes on the cell surface.…”
Section: Resultsmentioning
confidence: 99%